(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article talks about the scientific and civil views of a prominent representative of Kyrgyz linguistics, Academician B. Oruzbaev, on the issue of the state language. Attention is drawn to their relevance and practical value.